(untitled) (Journal of Health Sciences, 2018)
Introduction: Carcinoembryonic antigen (CEA) is used for monitoring of disease progression and treatment response in cancer patients. Our aim was to compare the performance of chemiluminescent microparticle immunoassay (CMIA) with electrochemiluminescence immunoassay (ECLIA) for CEA. Methods: A total of 115 samples were collected during routine diagnostic, prognostic and therapy monitoring procedures in patients with colorectal and pancreatic cancer. We used ARCHITECT i2000SR and Cobas E601 for CEA analysis in sera samples. Results: The correlation coefficient of 0.984 [95% CI: 0.972 to 0.991] for results obtained on both platforms was observed for CEA≤10 ng/mL group. Moreover, intercept of 0.9027 [95% CI: 0.705 to 1.099] and slope 0.8076 [95% CI: 0.765 to 0.8498] (p < 0.0001) was observed in this group. In CEA >10 ng/mL group we observed slope = 1.1986 [95%CI: 1.1474 to 1.2498] (p < 0.0001), intercept = -11.69 [-17.53 to - 5.84] and correlation coefficient of 0.985 [95% CI: 0.976 to 0.9914]. Mean differences between assays in group ≤10 ng/mL and >10 ng/mL were 0.2066 (95% CI: 0.0019 to 0.4113) and –2.66 (95% CI: -10.10 to 4.76) ng/mL, respectively. Conclusion: Although there were differences, based on 20 days precision tests, overall results showed a good analytical performance and correlation between CEA assays on ARCHITECT i2000SR and Cobas E601 platforms. Reference intervals appropriate for the method of CEA measurement should be used. The standardization and harmonization of serum CEA concentration assays are needed.